CO12 | Left internal carotid artery thrombosis in a patient with antiphospholipid antibody syndrome successfully treated with eculizumab (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Anti-phospholipid syndrome (APS) is characterized by thrombosis and pregnancy complications due to persistent anti-phospholipid antibodies, with stroke being the most common arterial thrombosis. The complement system has emerged as a key factor in APS-related events, offering potential for targeted therapies.